Implementasi Program Takhassus dalam Meningkatkan Kemampuan Hifẓu Al Qurʼān - Nazaruddin, Nazaruddin (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2024)
The Takhassus Al-Quran Program is a superior program intended for selected students based on their ability to read the Al-Quran correctly and fluently and by considering the agreement of students’ parents/ guardians to attend this program. This program is intended to focus students on the tahfizh Al-Quran which lasts for 6 months. One of the schools implementing the Takhassus program is Ar-Rabwah Islamic Junior High School, Indrapuri, Aceh Besar. This research was conducted to describe how the Takhassus tahfizh Al-Quran program at Ar-Rabwah Indrapuri Islamic Junior High School, Aceh Besar, which includes concepts and implementation. The approach used in this research is a qualitative approach with a case study design. Data collection was carried out by the researcher himself as the key instruments. Data collection was carried out through interview, observation, and documentation techniques and being analyzed through data reduction, data presentation, and conclusions. The results showed that in implementing Takhassus tahfizh Al-Quran program, Ar-Rabwah Islamic Junior High School carried out activities such as to make an entrance test in which students had to take an Al-Quran reading ability test before joining this program and made an agreement with the student's guardians; Takhassus tahfizh Al-Quran program is carried out by using a combined method, such as halaqah, tikrar, muraja'ah, and sima’i methods that were scheduled 4 times a day at the school mosque; and evaluations applied for this program were reading evaluations, daily deposit evaluations, weekly deposit evaluations, monthly deposit evaluations, and 6 monthly deposit evaluations.